Micron-scale vertical beam size measurements based on transition radiation imaging with a Schwarzschild objective; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Sukhikh L. G. Leonid Grigorievich; Artyukov I. Igor; Bajt S. Sasa; Kube G. Gero; Lauth W. Werner; Potylitsyn A. P. Alexander Petrovich; Vukolov A. V. Artem Vladimirovich (Transition Radiation, 2015)
Title screen.